Manajemen Keterampilan Membaca dan Menulis Mata Pelajaran Bahasa Indonesa di Sekolah Dasar - Murni Yanto (ESTETIK : Jurnal Bahasa Indonesia, 2018)
This article aimed to find out the implementation of reading and writing grade 1 students at State Elementary School number 02 Rejang Lebong. The type of research conducted is quantitative research. Quantitative research is a way of finding knowledge that uses numeric form as a means of finding information regarding what you want to know. The research population of class 1 students was 28 people. The samples used in this study were purposive samples, namely certain consideration techniques. The sample of this study was class 1 students of Rejang Lebong 02 Elementary School, which consisted of 14 people, consisting of 9 women and 5 men. Data collection using questionnaires and tests. Tests are used written tests and oral tests. The results obtained by this study were conducted through a questionnaire which concluded that the reading and writing skills of first grade students were high and low. Between variables x and y there is a strong or high correlation. With regard to the magnitude of r_xy which is 0.763, it ranges from 0.70-0.90, so it can be concluded that the hypothesis (Ha) has no effect on reading and writing class 1 Rejang Lebong or hypothesis (Ha) accepted, while the hypothesis (Ho) of reading ability and write or hypothesis (Ho) rejected.